Acceptability and adherence of Balanced Energy Protein (BEP) supplementation among pregnant women in Addis Ababa, Ethiopia: A Formative Study - Tigest Shifraw; Hanna Yemane Berhane; Sitota Tsegaye; Hanna Gulema; Hana Sime; Yoseph Yemane Berhane; Workagegnhu Tarekegn; Janaína Calu Costa; Dongqing Wang; Wafaie W. Fawzi; Yemane Berhane (PLoS ONE, 2026)
Background Balanced energy protein (BEP) supplements during pregnancy have shown promise in reducing small-for-gestational-age births and low birth weight in low- and middle-income countries, but practical gaps remain in implementing this supplementation. This formative study assessed the acceptability, adherence, and sharing practices of a ready-to-use BEP supplement among pregnant women in Addis Ababa, Ethiopia. Subjects and method From January to February 2023, 45 pregnant women were purposively selected from nine public health centers and provided a 4-week BEP supply with usage guidance. Thirty-nine participants completed in-depth interviews. The framework analysis focused on acceptability, adherence, and sharing. Adherence was calculated as the proportion of sachets consumed or returned empty; partially used or unopened sachets were considered unconsumed. Results Acceptability was high, with positive feedback on texture (32/39, 82.1%), smell (35/39, 89.7%), color (38/39, 97.4%), and ease of consumption (33/39, 84.6%). However, 23/39 participants (59%) found the taste overly sweet, which occasionally led to nausea or reduced intake. Over the one month, supplement consumption ranged from 0 to 30 sachets, with a mean intake of 21.9 (SD = 9.5). High adherence (≥80% consumption) was observed in 25/39 (64.1%) of participants. Intake was facilitated by provider counseling and family support, while fasting, travel, and weight concerns influenced consumption patterns. Sharing was minimal and discouraged through counseling. Most participants expressed willingness to continue supplementation, recommending reduced sweetness. Conclusion Pregnant women demonstrated high acceptability and adherence to the BEP supplement. Findings support its feasibility for informing intervention design in the main trial.